Aspired communities : Reconsidering community in light of the temporal dimensionality of social life - Posio, Pilvi (SAGE, 2025)
I argue in this article that our understanding of community is enhanced by examining the formation of collective aspirations for a shared future. Using examples from my fieldwork on long-term community recovery after the Great East Japan Earthquake in 2011 in the town of Yamamoto, I illustrate the potential of using the social process of collective aspiring as an analytical tool in theorizing and studying community. Instead of treating community as a particular grouping or identity, I approach the concept of community as a processual analytical frame for understanding various forms of sociality constituted by continuous and mutually constitutive enacting and envisioning within social practices. This practice approach not only overcomes the tensions between the agency, structure, actualization, and abstraction characteristic of conceptualizations of community, but also enables us to explore the significance of the future dimension of social life. The concept of future orientation of collective aspiring allows us to ethnographically grasp the contingent formation of community in the dynamic process of striving toward the desired futures in contrast to anticipation of uncertain futures. To capture the many aspects of this process, aspiring is explored as shared objectives, action-oriented pursuing, and affectively charged yearning. This proposed analytical tool sheds light on ever-evolving forms of sociality not only in their unity and togetherness but particularly in their ambiguities, conflicts, and power relations.